Language Strategy in a Merger Process - Sørensen, Puk Lundgaard (Language at Work - Bridging Theory and Practice, 2006)
There is no point in having a language strategy which merely collects dust on the shelf because it is out of touch with the reality in the company. The strategy must be used in everyday work so that it becomes a proper management tool. If Energinet.dk succeeds in doing so, the company will be able to use the language strategy to unite the company, with a concern to language and achieve a high qualitative level as well.